2017
DOI: 10.3892/mmr.2017.7144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined general-epidural anesthesia and total intravenous anesthesia on cellular immunity and prognosis in patients with non-small cell lung cancer: A comparative study

Abstract: The aim of the present study was to investigate the effects of combined general-epidural anesthesia (CGEA) and total intravenous anesthesia (TIVA) on cellular immunity and prognosis in patients with non-small cell lung cancer (NSCLC) in a Chinese population. One-hundred and twenty NSCLC patients were randomly divided into a TIVA group (n=60) and a CGEA group (n=60) using a random number table. All patients underwent video-assisted thoracoscopic surgery for radical resection. Blood pressure (BP) and peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
1
7
0
2
Order By: Relevance
“…The present study also compared T lymphocyte subsets in the two groups and found that all patients showed decreased levels of CD3 + , CD4 + , CD4 + /CD8 + and NK and increased CD8 + , but that these cells gradually recovered 3 days after surgery. A previous study has shown that anesthetics cause changes in the immune function of patients at any duration of administration (36), which was also verified by the results of the present study. It was also demonstrated that the immune function of the patient was inhibited after surgery and anesthesia, but returned to the original level with the recovery of the patient.…”
Section: Discussionsupporting
confidence: 92%
“…The present study also compared T lymphocyte subsets in the two groups and found that all patients showed decreased levels of CD3 + , CD4 + , CD4 + /CD8 + and NK and increased CD8 + , but that these cells gradually recovered 3 days after surgery. A previous study has shown that anesthetics cause changes in the immune function of patients at any duration of administration (36), which was also verified by the results of the present study. It was also demonstrated that the immune function of the patient was inhibited after surgery and anesthesia, but returned to the original level with the recovery of the patient.…”
Section: Discussionsupporting
confidence: 92%
“…Вона значно знижує частоту легеневих ускладнень, забезпечуючи хорошу аналгезію, покращуючи функцію діафрагми, знижуючи ймовірність розвитку й тяжкість післяопераційної гіпоксемії. Поліпшення респіраторних показників зумовлено не тільки блокадою сенсорних нервів, але й відновленням активності бронхіальних адренергічних рецепторів на тлі ЕА [22].…”
Section: результати та обговоренняunclassified
“…Qiang Xu et al (2017) вивчали вплив ЗА з ЕА та ТВА на клітинний імунітет і прогноз у хворих на недрібноклітинний рак легенів у Китаї. Вчені довели, що комбінована анестезія і ТВА впливали на клітинний імунітет, проте КА чинила менший вплив і покращувала післяопераційний знеболювальний ефект [23].…”
Section: результати та обговоренняunclassified
“…Anesthesia is most important for lung cancer patients undergoing surgical removal. Xu et al 2 compared the effects of total intravenous anesthesia (TIVA) and general anesthesia combined with epidural anesthesia on the cellular immunity and prognosis of patients undergoing thoracoscopic radical resection of non-small cell lung cancer (NSCLC). After the surgery, with either of the anesthesia methods, the number of T lymphocytes such as CD3(+), CD4(+) and CD8(+) T cell and the natural killer cells CD56(+) in the patients all decreased compared with the preoperative state, but the number of T lymphocytes and natural killer cells in the patients with general anesthesia combined with epidural anesthesia was higher than that in patients with TIVA.…”
Section: Types Of Anesthesiamentioning
confidence: 99%